Implementasi Pembelajaran STEM ESD Terintegrasi Robotik untuk Meningkatkan Keterampilan Berpikir Kreatif dan Komunikasi Siswa Sekolah Dasar. - Christina Lestari Retno Mahanani; Didit Ardianto; M. Zainal Arifin (Postgraduate, University of Mataram, 2026)
The study aims to analyze the effectiveness of the implementation of STEM ESD learning integrated with robotics in improving students' creative thinking and communication skills on environmental material. The study used a quasi-experimental method with a one-group pretest-posttest design for 118 sixth-grade students from four elementary schools in Bogor. The single-group design was chosen because the research focused on implementing learning innovations directly in the context of partner schools without changing the class divisions that have been established by the schools. The intervention was implemented over six meetings through ecosystem guard robot and trash cleaning robot projects that involved stages of environmental problem exploration, design, assembly, testing, and product presentation. Data were collected through creative thinking skills tests, peer assessments, observations, presentation assessments, and student interviews, then analyzed using descriptive statistics, the Wilcoxon test, and qualitative analysis. The results showed a significant increase in creative thinking skills with an average pretest score of 4.950 increasing to 7.710 in the posttest and an N-gain value of 0.688 (medium-high category). The highest increase occurred in the generate diverse ideas indicator with an N-gain of 0.864, followed by generate creative ideas at 0.645 and evaluate and improve ideas at 0.584. Communication skills also increased from an average pretest of 40.200 to 45.610 in the posttest with an N-gain of 0.304 (medium category). The communication aspects that experienced the most prominent improvement were the ability to discuss, convey ideas verbally, and collaborate in groups, while formal communication during presentations still needed strengthening. The Wilcoxon test results showed a significant difference between the pretest and posttest in creative thinking skills (Z = -8.536; p < 0.05) and communication (Z = -9.460; p < 0.05). Thus, project-based robotics-integrated STEM ESD learning is effective in improving elementary school students' creative thinking and communication skills while supporting the development of 21st-century competencies in a contextual and sustainable manner.